Norwegian-Somali parents who send their children to schools in Somalia - Paul Thomas (Cogent Education, 2016)
The perplexing numbers of Somali children withdrawn from schools in Norway and sent to Somalia is the concern of this study. These students are often brought back and re-enroll later as adolescents with concomitant educational challenges. The findings are critically analyzed employing John Ogbu’s cultural ecology of minorities and a CHAT-based inquiry that approaches the Somali community and Norwegian schooling as interconnected activities that share commonalities and yet evince several contradictions. The findings reveal the need to engage with Somali symbolic cultural artifacts (e.g. deen (religion), dhaqan (culture), gaal (the infidel or “Other”), and hisho (female modesty) and arrive at interpretations/understandings that are more amenable to educational success. It is argued that given the gravity and scale of the conundrum, both sides will have to think creatively if the aim is to safeguard the educational integrity of Somali children.